Potential of the Mangosteen Peel Extract (Garnicia mangostana L.) as a Bioreductor in the Synthesis of Copper Nanoparticles - Gladys Javani; Suyatno Sutoyo (Universitas Negeri Semarang, 2023)
The development of nanoparticle-based technology is currently of particular concern to scientists. This is because nanoparticles have many benefits in the health, industrial and food fields. The use of gold and silver metal-based nanoparticles has begun to be widely studied, but copper metal is still rarely developed. The manufacture of copper nanoparticles is carried out by synthesis using bioreductors derived from plants. Aquades extract of mangosteen rind (Garnicia mangostana L.) can be used as a bioreductor because it contains secondary metabolites that can reduce Cu ions during the synthesis process. This study aims to identify the secondary metabolites contained in mangosteen peel extract (Garnicia mangostana L.) and evaluate their potential as bioreductors through analysis using UV-Vis spectrophotometry. Phytochemical test results of mangosteen peel extract (Garnicia mangostana L.) showed positive results for flavonoids, saponins, phenolics, triterpenoids, and alkaloids. Alkaloid and phenolic compounds play a role in the reduction process of Cu ions so that they can be used as bioreductors. The results of the UV-Vis measurements showed a 1:1 ratio of extract and precursor; 1:2 ; 1:3 and 1:4 have a peak wavelength of 278 nm, where copper nanoparticles can form at a wavelength of 200-800 nm. At a ratio of 1:1 has the highest absorbance, namely 0.394. So that a 1:1 ratio has the potential to form CuNPs.